2018
DOI: 10.1097/sga.0000000000000279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Postoperative Feeding on the Recovery of Children Post Appendectomy

Abstract: The aim of this study was to determine the effect of early postoperative feeding on recovery after appendectomy in children. It was undertaken as a multicenter study. Patients were randomly assigned to 2 groups, each containing 46 children. Postoperatively, liquid and solid food intake and evacuation of first flatus and stool were recorded for the intervention and routine care groups. Postoperative thirst, hunger, nausea, and pain levels were evaluated at regular intervals using the Visual Analogue Scale. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Several reports have used the VAS to evaluate the degree of thirst in pediatric patients. However, the appropriate VAS method for pediatric patients aged ≤ 10 yr has not been fully established ( 20 , 21 , 22 , 23 ). Based on our experience with the present case, we identified two important factors when using the VAS to evaluate OTT in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have used the VAS to evaluate the degree of thirst in pediatric patients. However, the appropriate VAS method for pediatric patients aged ≤ 10 yr has not been fully established ( 20 , 21 , 22 , 23 ). Based on our experience with the present case, we identified two important factors when using the VAS to evaluate OTT in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive postoperative planning, which includes aspects like nutrition, excretory mobilization, and pain relief, is pivotal for recovery 5,10,22,23 and can reduce the duration of hospitalization. 24 It is crucial to initiate nutrition early, and this decision should be based on the perforation status. 25 In our study, feeding began on the first postoperative day.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, satisfaction with the fasting protocol was greater for the ERAS group than for the conventional group. Other published studies have also reported benefits of a shorter duration of perioperative fasting on patient comfort[ 25 - 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative fasting can induce discomfort and anxiety in children due to thirst and hunger. Furthermore, early postoperative feeding in children has been reported to reduce the levels of hunger, thirst, and pain, shorten the time to first flatus/stool, and decrease infection rates, without increasing the incidence of vomiting[ 25 - 27 ]. Nevertheless, most hospitals still abide by the strategy of restricting food intake until ≥ 6 h after surgery.…”
Section: Introductionmentioning
confidence: 99%